Analisis Masalah Pengelolaan Kawasan Perbatasan Antara Provinsi Nusa Tenggara Timur (NTT) Dan Negara Timor Leste - Kathrine Maharani Mamengko; Engelbertus Tobu; Yohanes Arman (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Border area management has always been an interesting topic of discussion, this was proven when the issue of border area development became one of the agendas in the national development plan. National borders have strategic significance for Indonesia, especially in terms of defense-security, economy-trade and socio-culture. This article is an attempt to describe the management of land border areas in East Nusa Tenggara. The land border area for the province of East Nusa Tenggara, which is directly adjacent to the neighboring country of Timor Leste. The adjacent position allows for cross-border interactions and activities between communities in the land border area. With all the potential it has, the border area in East Nusa Tenggara has enormous potential to be developed, so that appropriate policies and management are needed so that the expectations of the government and society to make the border area a center of new economic growth can be realized.